Amino Acid Supplementation to Reduce Environmental Impacts of Broiler and Pig Production: A Review - Cappelaere, Léa; Le Cour Grandmaison, Josselin; Martin, Nicolas; Lambert, William (Frontiers in Veterinary Science, 2021)
Poultry and swine farming are large contributors to environmental impacts, such as climate change, eutrophication, acidification and air and water pollution. Feed production and manure management are identified as the main sources of these impacts. Reducing dietary crude protein level is a nutritional strategy recognized to both decrease the use of high impact feed ingredients and alter manure composition, reducing emissions of harmful components. For a successful implementation of this technique, feed-grade amino acid supplementation is crucial to maintaining animal performance. Reducing crude protein lowers nitrogen excretion, especially excess nitrogen excreted in urea or uric acid form, improving nitrogen efficiency. At feed-gate, low crude protein diets can reduce the carbon footprint of feed production, through changes in raw material inclusion. Magnitude of this reduction mainly depends on the climate change impact of soybean meal, and its Land-Use change, and on feed-grade amino acids used. Reducing dietary crude protein also lowers environmental impact of manure management in housing, storage and at spreading: nitrogen emissions from manure (ammonia, nitrates, nitrous oxide) are reduced through reduction of nitrogen excretion. Moreover, synergetic effects exist with nitrogen form, water excretion and manure pH, further reducing emissions. Volatilization of nitrogen is more reduced in poultry than in pig but emissions have been more studied and are better understood for pig slurry than poultry litter. Ammonia emissions are also more documented than other N-compounds. Low crude protein diets supplemented with amino acids is a strategy reducing environmental impact at different stages of animal production, making Life Cycle Assessment the best suited tool to quantify reduction of environmental impacts. Recent studies report an efficient reduction of environmental impacts with low crude protein diets. However, more standardization of limits and methods used is necessary to compare results. This review summarizes the current knowledge on mitigation of environmental impacts with low crude protein diets supplemented with amino acids in poultry and swine, its quantification and the biological mechanisms involved. A comparison between pigs and poultry is also included. It provides concrete information based on quantified research for decision making for the livestock industry and policy makers.